Healthcare emergency incident management operations guide - Glarum, Jan F. (Butterworth-Heinemann, 2017)
Healthcare Emergency Incident Management Operations Guide offers healthcare personnel a quick and intuitive guide to preparing for, responding to and recovering from events which have the potential to impact their operations. The recently updated Centers for Medicaid & Medicare Services (CMS) rules for emergency preparedness added 10-15 new healthcare organizations into the mix that require emergency preparedness efforts. The Hospital Incident Command System (HICS) is a good tool for event management but, like all tools, it requires practice. Many hospital personnel take online ICS courses and rarely practice enough to be proficient. This is a comprehensive guide to the HICS and can be referenced during initial and refresher training as well as during event management.--Provided by publisher.